Heat-shock protein peptide complex–96 vaccination for recurrent glioblastoma: a phase II, single-arm trial. Issue 2 (12th December 2013) - Bloch, Orin; Crane, Courtney A.; Fuks, Yelena; Kaur, Rajwant; Aghi, Manish K.; Berger, Mitchel S.; Butowski, Nicholas A.; Chang, Susan M.; Clarke, Jennifer L.; McDermott, Michael W.; Prados, Michael D.; Sloan, Andrew E.; et al.
Abstract: Background: Outcomes for patients with recurrent glioblastoma multiforme (GBM) are poor and may be improved by immunotherapy. We investigated the safety and efficacy of an autologous heat-shock protein peptide complex–96 (HSPPC-96) vaccine for patients with recurrent GBM. Methods: In this open-label, single-arm, phase II study, adult patients with surgically resectable recurrent GBM were given vaccine after gross total resection. The primary endpoint was overall survival at 6 months. Secondary endpoints included overall survival, progression-free survival, safety, and immune profiling. Outcome analyses were performed in the intention-to-treat and efficacy populations. Results: Between October 3, 2007 and October 24, 2011, 41 patients underwent gross total resection of recurrent GBM and received a median of 6 doses of HSPPC-96 vaccine. Following treatment, 90.2% of patients were alive at 6 months (95% confidence interval [CI]: 75.9–96.8) and 29.3% were alive at 12 months (95% CI: 16.6–45.7). Median overall survival was 42.6 weeks (95% CI: 34.7–50.5). Twenty-seven (66%) patients were lymphopenic prior to therapy, and patients with lymphocyte counts below the cohort median demonstrated decreased overall survival (hazard ratio: 4.0; 95% CI: 1.4–11.8; P = .012). There were no treatment-related deaths. There were 37 serious (grades 3–5) adverse events reported, with 17 attributable to surgical resection and a single grade 3 constitutional event related to the vaccine. Conclusion: The HSPPC-96 vaccine is safe and warrants further study of efficacy for the treatment of recurrent GBM. Significant pretreatment lymphopenia may impact the outcomes of immunotherapy and deserves additional investigation.